2009
DOI: 10.1158/0008-5472.can-08-4859
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Rigidity of the Extracellular Matrix Regulates the Structure, Motility, and Proliferation of Glioma Cells

Abstract: Glioblastoma multiforme (GBM) is a malignant astrocytoma of the central nervous system associated with a median survival time of 15 months, even with aggressive therapy. This rapid progression is due in part to diffuse infiltration of single tumor cells into the brain parenchyma, which is thought to involve aberrant interactions between tumor cells and the extracellular matrix (ECM). Here, we test the hypothesis that mechanical cues from the ECM contribute to key tumor cell properties relevant to invasion. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
765
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 809 publications
(839 citation statements)
references
References 51 publications
58
765
0
1
Order By: Relevance
“…This simplication, while useful, is not very realistic: it is known that some parts of cells still adhere while others lose contact. 18,51,59 In other words, inhomogeneously distributed force affects the adhesion and provides a feedback on the overall shape and motion. This is remedied here, in contrast to ref.…”
Section: Complex Modes Of Movementmentioning
confidence: 99%
“…This simplication, while useful, is not very realistic: it is known that some parts of cells still adhere while others lose contact. 18,51,59 In other words, inhomogeneously distributed force affects the adhesion and provides a feedback on the overall shape and motion. This is remedied here, in contrast to ref.…”
Section: Complex Modes Of Movementmentioning
confidence: 99%
“…Cells may respond to the mechanical properties of their ECM, such as substrate stiffness, by differentiation, proliferation and/or apoptosis [22,23,31,67]. Experiments demonstrate that a specific deformation range sensed by a cell leads to a specific differentiation [10,34,69].…”
Section: Cell Differentiation Proliferation and Apoptosismentioning
confidence: 99%
“…To avoid such abnormal conditions, cells have to be particularized in such a way as to differentiate or proliferate in response to appropriate biological stimuli. Experiments have shown that, besides other factors [58,59], the mechanical structure of cellular micro-environments plays an important role in cell differentiation and proliferation [22,23,31,67]. For instance, Mesenchymal Stem Cells (MSCs) differentiate into specific phenotypes with high sensitivity to the tissue rigidity where they reside in.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been long understood that soluble factors from the cellular microenvironment can strongly influence cellular behavior, it is becoming increasingly clear that physical, and especially mechanical, inputs can also affect cell behaviors such as migration, proliferation, and differentiation (1)(2)(3)(4). Cells frequently respond to mechanical stimuli by adaptively tuning their intrinsic mechanical properties, and significant evidence suggests that this ''mechanoadaptation'' is key to transducing these inputs into biochemical signals that mediate cell behavior.…”
Section: Introductionmentioning
confidence: 99%